Biomechanical evaluation of malleable noncompression miniplates in mandibular angle fractures: an experimental study - DOLANMAZ, DOĞAN; Esen, Alparslan; Dolanmaz, DOĞAN; Tuz, Hakan Hifzi (My University, 2012)
The purpose of this experimental study was to test the reliability of a single malleable titanium miniplate using Champy-s method of fixing fractures of the mandibular angle. Eighteen sheep hemimandibles were used to evaluate 2 plating techniques. The groups were tested with either a single non-compression titanium miniplate or a single malleable titanium miniplate. A cantilever bending biomechanical test model was used for the samples. Each group was tested with vertical forces using a servohydraulic testing unit. The displacement values in each group at each 10 N stage up to 90 N were compared using 2-way analysis of variance (ANOVA). The displacement values for the 2 groups differed significantly (p < 0.01). The variance analyses showed that the biomechanical behaviour of a single non-compression miniplate was better than that of a single malleable miniplate. The non-compression miniplate fixed by screws had greater resistance to occlusal loads than the malleable plate fixed by screws, and the malleable plate alone was not sufficient to withstand the early postoperative bite force. (C) 2011 The British Association of Oral and Maxillofacial Surgeons. Published by Elsevier Ltd. All rights reserved.